Digital Intelligence Empowerment and Cross - domain Synergy: Research on the Construction of Supply Chain Financing Ecology in Chengdu - Chongqing Twin-city Economic Circle from the Perspective of Digital Government Financial Innovation Governance - Wang, Xiaoyu; Wang, Zihao (Journal of Social Science and Humanities, 2025)
The Chengdu-Chongqing Twin Cities Economic Circle has close industrial ties, but the financing problems of supply chain enterprises in different places have limited their development. This study proposes an innovative supply chain financing ecological construction model of “digital intelligence empowerment and cross-domain cooperation”. The model is led by the Chengdu-Chongqing government, which builds a digital supply chain financing platform, integrates the resources of local banks, and achieves information sharing and business synergy. It uses digital financial technology to streamline the credit process, strengthen risk management and control, and provide efficient and convenient financing services to overseas supply chain enterprises. This model not only helps alleviate the pressure of enterprise financing and promotes the economic growth and synergetic development of the Chengdu-Chongqing Twin Cities Economic Circle but also provides new perspectives and practical examples for research in the field of supply chain finance, which has a certain universality and promotional value.